Manajemen Dosen Penasehat Akademik dalam Meningkatkan Motivasi Kuliah Mahasiswa - Mardotella Mardotella; Irwan Fathurrochman; Sugiatno Sugiatno; Hamengkubuwono Hamengkubuwono; Muhammad Amin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the management of academic advisors lecturers in increasing the motivation of college students MPI STAIN Curup. The research method in this study uses qualitative research methods. The results of the study show that management carried out by academic advisor lecturers in increasing student motivation for STAIN Curup Islamic Education Management students is by making planning (lecturers and students jointly make student study plans), organizing (division of balanced academic advisor lecturers), actuating (Academic advisors are more active in carrying out their duties), and controlling (Academic advisors supervise students). Conclusion, Supporting factors for academic advisors in increasing MPI student motivation are divided into two, namely encouragement from within (desire, individual traits, awareness, past experience) and encouragement from outside (praise and prizes, rules / regulations, coercion, coercion, role model, knowing the results, competition / competition), while the inhibiting factors are time management, space, busyness, parents, and students. Keywords: Management, Motivation, Academic Advisor Lecturers.